Implementation of the Holistic Education Approach in Inclusive Schools based on School Culture in Senior High Schools - Rupiah Rupiah; Nursyamsiah Nursyamsiah; Bagus Endri Yanto (STAI Hubbulwathan Duri, 2025)
Inclusive schools require comprehensive educational services that support all aspects of student development. Holistic education nurtures students' intellectual, emotional, physical, social, aesthetic, and spiritual capacities. This study explores how school culture influences the implementation of holistic education in inclusive educational settings. A qualitative descriptive method with a case study approach was employed. Data were collected through interviews and observations, with purposive sampling used to select participants. The validity of the research instrument was assessed using the Aiken index, and reliability was measured with Cronbach’s alpha. Data were analyzed through reduction, presentation, and conclusion drawing. Findings revealed that school culture plays a critical role in shaping holistic education practices. Core cultural values—such as religious beliefs, leadership, environmental stewardship, and discipline—are embedded into daily routines, including regular prayer, cleanliness, and a sense of responsibility. These practices promote consistent and meaningful integration of holistic values into the learning environment. The study highlights how school culture can facilitate the practical application of holistic education in inclusive schools. Educators and administrators can use these insights to foster environments that support diverse student needs through cultural reinforcement. This research offers a valuable reference for teachers, researchers, and education practitioners interested in holistic education. Future studies should aim to design holistic education models that include quality assurance measures and explore multicultural approaches to inclusive service delivery.